Exploration of the Themes and Vocabularies of English Books by Kindergarten Students - Sri Slamet; Markhamah Markhamah; Heriyanti Tahang; Choiriyah Widyasari; Sri Katoningsih; Aisyah Rahmah I; Hilyatul Millah; Salma Zhafirah Yasri; Rellive Enka Banuvita (Research Synergy Foundation, 2025)
One important aspect of learning English in kindergarten is vocabulary mastery, which plays a crucial role in children’s ability to communicate effectively and understand language. However, many children at Aisyiyah Kindergarten in Surakarta, which were observed through purposive sampling, still struggle with vocabulary acquisition. It was found that the learning media, primarily textbooks, focused mostly on activities such as coloring, thickening, and writing letters, without providing sufficient repetition exercises to reinforce vocabulary. This was identified as a significant factor contributing to the challenges children face in retaining vocabulary. The recent research objective was to explore the themes and vocabulary in the textbooks in Surakarta kindergartens. This study specifically sought to examine how well textbooks support the development of vocabulary mastery and whether the content is culturally appropriate and engaging for young learners. The research was conducted using an exploratory qualitative descriptive approach. Data were collected through document analysis of English textbooks used in Surakarta kindergartens, applying first-order and second-order understanding techniques to identify and categorize themes and vocabulary. The results revealed that the textbooks used in these kindergartens were thematic, with some themes aligning with the Ministry of National Education's guidelines. However, the vocabulary introduced was sometimes disconnected from the children’s everyday experiences and was occasionally culturally inappropriate. While some textbooks included a significant amount of vocabulary, the frequency of repetition exercises was insufficient, with some books lacking repetition altogether.